Diversity of Soil Fauna in the Sesaot Nature Tourism Forest, West Lombok - Mohammad Liwa Ilhamdi; Agil Al Idrus; Muhamad Syazali (Jurnal Biologi Tropis, 2022)
The Sesaot Nature Tourism Forest Area is a tourist area and an area that is used for the production of several plantation commodities, along with increasing human activities in the Sesaot Nature Tourism Forest area, it raises questions related to the state of its ecosystem, one aspect that reflects the state of the ecosystem, namely the diversity of soil fauna. The sample locations are divided into three paths based on the characteristics of the ecosystem, namely the waterway which is niche points located along the river flow, the middle lane in the form of a path around a forest area filled with large tree stands, and the edge lane which is a path located in the middle of the river around residential areas and rice fields. The purpose of this study was to determine the index of diversity, evenness of species, and species richness of soil fauna in the Sesaot Nature Tourism Forest. Sampling of soil fauna using the pitt fall trap method is placed along 3 predetermined paths. The results showed that in the Sesaot Nature Tourism Forest, there were at least 30 types of soil fauna dominated by the Formicidae family. The highest soil fauna diversity index was found in the waterway with 2.24, followed by the edge lane at 2.22, and the middle lane at 1.13. The evenness value of soil surface fauna species in the Sesaot Nature Tourism Forest in the waterway is 0.66, followed by 0.65 in the edge lane, and 0.33 in the waterway. The highest value of species richness (Margalef index) was found in the waterway with 3.26, followed by the edge and middle lane with 2.69.